Student information preferences and the role of social media in Indonesian higher education - Prabawangi, Rani Prita; Fatanti, Megasari Noer; Nasih, Ahmad Munjin (Universitas Padjadjaran, 2026)
Background: Research has well documented how social media acts as a primary information source for both enrolled and prospective students. However, universities often lack clear, evidence-based guidance on how to engage their internal and external audiences. This knowledge gap forces university public relations (PR) teams to rely on trial and error, often struggling to create impactful content. Purpose: This study investigates student preferences for social media content and information sources to enlighten university PR staff who want to improve their institutional communication. Methods: This research employed a mixed-methods approach, combining a quantitative survey of 330 students with qualitative insights gathered from focus group discussions (FGDs) and in-depth interviews with 150 students. The survey included current students because they were once prospective students, so they could give insights as both prospective and current students. Results: Students trust unofficial sources (such as community accounts) and direct recommendations from those closest to them more than official university channels. They are also much more interested in authentic, story-based content. Conclusions: The implications of these findings suggest that, to increase engagement and institutional image, campus social media teams should consider presenting story-based content and increasing audience interactivity. Implications: To strengthen their image and engagement, the teams need to prioritize story-based content, amplify credible community voices, and increase two-way engagement. Universities are also advised to create secondary accounts to post more entertaining and light-hearted content to reduce audience reliance on unofficial sources, and or collaborate with community-driven accounts.